A methodology for assessing deployment trauma and its consequences in OEF/OIF/OND veterans: The TRACTS longitudinal prospective cohort study - McGlinchey, Regina E.; Milberg, William P.; Fonda, Jennifer R.; Fortier, Catherine Brawn (International journal of methods in psychiatric research, 2017)
Many US veterans of Afghanistan and Iraq have multiple physical and psychiatric problems. A major focus of research has been on determining the effects of mild Traumatic Brain Injury (mTBI), but mTBI is rarely diagnosed in the absence of co‐occurring conditions such as blast exposure, post‐traumatic stress disorder (PTSD), depression, substance abuse, etc. These potentially interactive psychological and physical conditions produce complex patterns of cognitive, psychological, and physical symptoms that impede civilian reintegration and complicate efficient and effective treatment planning. The Translational Research Center for TBI and Stress Disorders (TRACTS) has developed a multidisciplinary approach to the assessment of deployment trauma and its consequences in veterans of these wars. The prospective TRACTS longitudinal cohort study conducts state‐of‐the‐art assessments in the domains of biomedical function, lifetime head trauma, psychological function encompassing deployment experience and lifetime exposure to traumatic events, neuropsychological function, and structural and functional neuroimaging. The TRACTS longitudinal cohort study is the first of its kind to comprehensively evaluate lifetime incidence of TBI and PTSD in these veterans, in addition to those incurred during military deployment. The protocol has begun to reveal information that will help improve understanding of the complex pathophysiology associated with co‐occurring mTBI and related stress disorders.